1998
DOI: 10.1191/026921698674125048
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between opioid use and laxative use in terminally ill cancer patients

Abstract: The frequency of the use of laxatives, and the relationship between doses of laxatives and of opioid analgesia, were determined by a prospective study of 498 hospice inpatients with advanced cancer. Laxatives were required by 87% of patients taking oral strong opioids, 74% of those on weak opioids and 64% of those not receiving opioid analgesia. The form of the relationship appears to be hyperbolic, as suggested by the presentation of the results arranged by opioid quartile and by the improved correlation obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
99
1
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(106 citation statements)
references
References 7 publications
1
99
1
5
Order By: Relevance
“…Several types of pharmacological agents are available for treating OIC including stool softeners, bowel stimulants and bulk laxatives [14] . In a survey of 498 terminally ill cancer patients receiving strong opioids, 87% were also receiving laxatives [32] . It is widely advised that laxatives should be started concurrently with opioids; however, a study which assessed laxative prescribing in patients receiving a first prescription for a strong opioid showed that only 37% of patients started taking laxatives within 5 days of starting opioid therapy [33] .…”
Section: Current and Future Treatments For Oicmentioning
confidence: 99%
“…Several types of pharmacological agents are available for treating OIC including stool softeners, bowel stimulants and bulk laxatives [14] . In a survey of 498 terminally ill cancer patients receiving strong opioids, 87% were also receiving laxatives [32] . It is widely advised that laxatives should be started concurrently with opioids; however, a study which assessed laxative prescribing in patients receiving a first prescription for a strong opioid showed that only 37% of patients started taking laxatives within 5 days of starting opioid therapy [33] .…”
Section: Current and Future Treatments For Oicmentioning
confidence: 99%
“…Noch ein drucks vol ler wer den die se Anga ben, wenn aus schließ lich Pa ti en ten im Rah men der Tu mor schmerz the ra pie oder Pal lia tiv me di zin be trach tet wer den. Sy kes [46] be rich te te über Obsti pa ti on bzw. erfor der li chen La x an zi enein satz bei 87 der Pa ti en ten ei nes Hos pi zes, die stark wirk same Opioide er hiel ten.…”
Section: Opioide Und Obsti Pa Ti Onunclassified
“…Laxanzien wurden bei 70,4% der Patienten mit einer Morphintherapie eingesetzt. Diese Zahl steht im Einklang mit den Resultaten einer prospektiven Studie von Sykes, die die Notwendigkeit einer Laxanzientherapie bei bis zu 87% der Patienten mit stark wirksamen Opioiden herausstellt [20]. Die morphinbedingte Obstipationsrate entsprach den Literaturangaben [8].…”
Section: Morphinunclassified